Mr. Koala's steam train. (Brookfield, CT : Brainwaves Ltd., 1997)
Mr. Koala is building a train. Find all the shapes he needs to build his steam train unti Toot! Toot! is ready to go!
Keywords: Shapes -- Fiction; Children stories